Peran Lembaga Penjamin Simpanan Dalam Pengelolaan Sistem Stabilitas Keuangan Indonesia - Rudy Susanto; Zainal Arifin H. Masri (STIE Mandala Jember, 2020)
The purpose of the study is to find out: (1) The purpose of financial system stability; (2) Indicators used to declare financial system instability; (3) The work mechanism of the financial system stability committee; (4) Role and function of the IDIC in participating in managing financial system stability; (5) The maximum value of deposits guaranteed by LPS; (6) Many banks are included in the LPS oversight and actions taken by the LPS. This research uses the case study method with qualitative descriptive analysis. The results of the study: (1) There is no standard definition of financial system stability that is accepted by the international world, but at least a stable, healthy and strong financial system is able to allocate sources of funds, perform intermediary functions, carry out payments, spread risk well, prevent and resistant to disruption to the real sector and financial system; (2) There are 2 indicators, namely prudential microeconomic and macroeconomic; (3) KSSK has the duty to oversee economic indicators so that financial system stability is achieved; (4) DIC functions to guarantee customer deposits and handle failed banks; (5) Deposit guaranteed by LPS is a maximum of Rp 2 billion; (6) In 2019 there were 100 banks handled by LPS. An unstable financial system will affect the stability of the overall economic system. LPS has succeeded in arousing public trust to save. Keywords: Financial System Stability, Financial System Crisis, KSSK, LPS